(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, in the conditions of the new Uzbekistan, the issues of state support for the development of culture in enterprises and organizations and the issues of improving the quality of personnel are covered in detail. you will get acquainted with the recommendations.